Which Cannulation Technique for Which Patient. Issue 7 (May 2014) - Gallieni, Maurizio; Brenna, Irene; Brunini, Francesca; Mezzina, Nicoletta; Pasho, Sabina; Fornasieri, Alessandro
Cannulation of arteriovenous (AV) access is a crucial part of vascular access management in hemodialysis patients. It can significantly affect survival of the AV access, and consequently, it probably influences patient survival. The best type of cannulation technique, rotating site versus constant site (or buttonhole), is currently debated, but the increase in infectious complications observed with the buttonhole technique suggests a prudent use of this technique, restricting it to specific patients. Even in cases with a specific indication, the balance between advantages of the constant site needling and the potentially severe consequences of access related systemic infection should be considered. Educational efforts in improving cannulation skills of dialysis staff are important for improving outcomes, as the proper use of the rotating site technique might still be the best approach to cannulation.